MEKANISME PENERAPAN PAJAK PARKIR PADA PT BARRU BARAKAH PROPERTI - Uswatun Khasanah Wirayanti; Ilham Ilham; Veronika Sari Den Ka (Politeknik Bosowa, 2021)
The purpose of this study is to determine how the calculation, payment and reporting of Parking Tax on PT Barru Barakah Property and to find out whether PT Barru Barakah Property as a Taxpayer, Parking Tax has carried out its tax obligations in accordance with applicable tax regulations . This research used descriptive qualitative analysis techniques. The data of this study were obtained from the results of direct interviews with the tax staff of PT Barru Barakah Properti and Employees of the UPTD KTU Parking Area of the Makassar City Revenue Agency. The results of this study indicate that the calculation mechanism has been carried out by multiplying the tax base with the rate of thirty percent applicable in the Makassar city area, the mechanism for depositing and reporting parking tax has been carried out on time in accordance with applicable regional regulations. PT Barru Barakah Properti as a parking taxpayer has carried out its tax obligations in accordance with the applicable taxation regulations, namely Law Number 28 of 2009 and Regional Regulation of Makassar City Number 2 of 2018 concerning Regional Taxes.Keywords: Calculation, Payment, Reporting, Parking Tax, Regional Tax